2018
DOI: 10.1080/02670844.2017.1320862
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of characterisation of plasma electrolytic oxidation coatings on carbon steel prepared from aluminate and silicate electrolytes

Abstract: Two kinds of PEO coatings were prepared on low carbon steel from aluminate electrolyte and silicate electrolyte, respectively. The coating surface and cross-section morphologies were observed by scanning electron microscope. The elemental and phase compositions were investigated by energy-dispersive spectrometer and X-ray diffraction, correspondingly. The scratch test was employed to examine the adhesion of the PEO coating. The electrochemical tests were used to evaluate the anti-corrosion property of PEO coat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 22 publications
(28 reference statements)
0
6
0
Order By: Relevance
“…Nowadays, light metals such as titanium [1][2][3][4], niobium [5][6][7][8][9], tantalum [10][11][12][13][14][15], and their alloys [16][17][18][19][20][21][22], after electrochemical treatment (electropolishing and/or plasma electrolytic oxidation), may be used as biomaterials (implant materials) because of their mechanical properties [23][24][25][26][27], good corrosion resistance [28][29][30][31] in body fluids, and osteointegration [32][33][34]. The electropolishing…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, light metals such as titanium [1][2][3][4], niobium [5][6][7][8][9], tantalum [10][11][12][13][14][15], and their alloys [16][17][18][19][20][21][22], after electrochemical treatment (electropolishing and/or plasma electrolytic oxidation), may be used as biomaterials (implant materials) because of their mechanical properties [23][24][25][26][27], good corrosion resistance [28][29][30][31] in body fluids, and osteointegration [32][33][34]. The electropolishing…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Malinovschi et al [ 29 ] developed uneven, porous films in an electrolyte containing Na 2 SiO 3 and Na 2 CO 3 , formed mainly by amorphous SiO 2 , Fe 2 O 3 , and Fe 3 O 4 . However, Yang et al [ 30 ] compared aluminate and silicate electrolytes for growing anodic films in low carbon steel and evaluated their corrosion resistance. In this study, both anodic coatings showed a more positive corrosion potential and a lower corrosion current density than the substrate in 3.5% NaCl; but the layer developed in the aluminate condition (10 g/L NaAlO 2 and 1.5 g/L NaH 2 PO 4 ⦁2H 2 O) had a denser structure with better anti-corrosion properties.…”
Section: Introductionmentioning
confidence: 99%
“…Amongst the most current reports found in the literature, the creation of protective barriers using plasma technologies stands out, be it the so-called hot plasma, or the one characterized as cold plasma, in which the substrates temperature remains close to the environmental 13 . In this context, some works use plasma electrolytic oxidation (PEO) techniques 1,2,14,15 and their variants 16,17 ; plasma transferred arc (PTA) 18 and thermal spray [19][20][21] , techniques in which the substrate usually reaches high temperatures. Other report deposition processes in low-pressure plasma 5,13,22 and in atmospheric-pressure plasma 22 .…”
Section: Introductionmentioning
confidence: 99%
“…Concerning the aforementioned techniques, most of them present as the main disadvantage the fact that the process develops at high temperatures 3,14,16,17 , limiting the treatment to heating resistant substrates. Also, the authors frequently report the presence of pores and cracks in PEO deposited coatings 1,3,14 , as well as adhesion problems and de-coating of the oxide layer formed on the treated metal 3 , characteristics that hinder the protection against corrosion.…”
Section: Introductionmentioning
confidence: 99%